Geoengineering and the Approach of International Environmental Documents Towards It's Regulation - Zahra Mahmoudi Kordi; Masume Gholami Miansarayi (Faṣlnāmah-i Pizhūhish-i Huqūq-i ̒Umūmī, 2022)
Climate change is considered to be the biggest crisis of the present era, and traditional approaches have not been very effective to deal with it yet. Thus, in recent decades, geoengineering which includes two main methods of carbon dioxide removal and solar radiation management has come to the attention of countries. Like other emerging technologies, besides its benefits, most important of which to combat climate change, due to scientific uncertainty, they might have harmful effects on the environment. The present article has aimed to describe geoengineering methods and their environmental pros and cons. The findings of the article show that although the geoengineering methods in international environmental treaties are scattered, mostly in the form of implicit expressions, the rules and the actions of member states indicate the different and sometimes contradictory attitudes toward geoengineering, which varies from explicit or implicit approval of some methods, especially in treaties related to climate change, to explicit and implicit opposition of others, such as the Convention on Biological Diversity, the London Protocol, and the Ozone Conservation Convention. This dispersion is so great that a specific legal system cannot be assumed.